Determining the Dominant Variable in Budgeting on Performance Effectiveness / PT (Persero) Indra Karya All Branches in Indonesia - Andreano, Pillipus Resar (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
The purpose of this study was to investigate the effect of service quality and patient trust on patient loyalty mediated by patient satisfaction in patients who hospitalized at “CDE” Hospital, Bogor, West Java. A Google Forms online survey on inpatients at "CDE" Hospital, Bogor, West Java was used to collect the data of this study. Data analysis was performed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method to measure the relationship between variables with the help of Smart PLS 3.0 software. The results of the study prove that service quality has not a positive and significant effect on patient loyalty. Other results prove that patient trust has a positive and significant effect on patient loyality, service quality has a positive and significant effect on patient satisfaction, patient trust has a positive and significant effect on patient satisfaction, patient satisfaction has a positive and significant effect on patient loyality, service quality has a positive and significant effect on patient loyality mediated by patient satisfaction, and patient trust has a positive and significant effect on patient loyality mediated by patient satisfaction.